Factors Related to Methadone Maintenance Treatment Outcome at Princess Mother Institute on Drug Abuse Treatment - Duangsoithong, Thiti; Chaipichitpan, Nanta (Journal of The Department of Medical Services, 2022)
Background: Opioids are highly dangerous substances. When an individual takes this drug unintentionally, itcan result in severe addiction. Methadone maintenance treatment is the main concept used to help patients reduceor quit the use of drugs and increase their quality of life. Objective: The purpose was to study the outcomes ofmethadone maintenance treatment at the methadone clinic in PMNIDAT. Method: This study was a retrospectivedescriptive study which had been implemented by applying medical record reviews of opioid addicts in the clinicfrom 2017 to 2021 (5 fiscal years). The data had been collected from 320 samples between 27th April to 31st May2022, using personal data records and treatment forms. The tool quality was examined by 3 experts with I-CVI(0.8) – 1.0, S-CVI (0.97) and by Cronbach’s alpha coefficient (0.83). The data were analyzed and shown by number,percentage, mean and standard deviation. The statistical analysis was implemented by using Chi-Square and Fisher’sexact test at the statistical significance level .05. Result: 41.3% of patients could reduce using heroin and 21.9%could quit using the drug. However, 28.8% of the patients remain in the treatment regimen, and 72.5% of them havereturned to work and study. The factors affecting the treatment outcomes were personal factors, which were age,occupation, education, marital status, history of opioid drug use, and incomes. The therapeutic factors were dailydose of methadone and the length of therapy stay. Conclusion: The treatment could result in good outcome ifenhanced by supporting factors, such as individual factors (age, occupation, and education). The therapeutic factorswere receiving enough dose of methadone and an appropriate length of treatment. Thus, to develop the mosteffective treatment system for this group of patients, therapists should use this information to develop an individualtreatment plan based on each patient’s conditions.